2020
DOI: 10.3390/ijms21218053
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electromagnetic Fields Stimulate HIF-1α-Independent VEGF Release in 1321N1 Human Astrocytes Protecting Neuron-like SH-SY5Y Cells from Oxygen-Glucose Deprivation

Abstract: Pulsed electromagnetic fields (PEMFs) are emerging as an innovative, non-invasive therapeutic option in different pathological conditions of the central nervous system, including cerebral ischemia. This study aimed to investigate the mechanism of action of PEMFs in an in vitro model of human astrocytes, which play a key role in the events that occur following ischemia. 1321N1 cells were exposed to PEMFs or hypoxic conditions and the release of relevant neurotrophic and angiogenic factors, such as VEGF, EPO, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Furthermore, its effect has been proved in many cell types of the neurovascular unit. In this context, most in vitro studies are focused on neurons and microglia ( Vincenzi et al, 2017 ; Gessi et al, 2019 ; Merighi et al, 2020 ) and to a lesser extent on endothelial cells ( Font et al, 2019 ) and astrocytes ( Vincenzi et al, 2020 ). No studies have been reported analyzing the effect of PEMF on oligodendrocytes and pericytes which are also part of the neurovascular unit.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, its effect has been proved in many cell types of the neurovascular unit. In this context, most in vitro studies are focused on neurons and microglia ( Vincenzi et al, 2017 ; Gessi et al, 2019 ; Merighi et al, 2020 ) and to a lesser extent on endothelial cells ( Font et al, 2019 ) and astrocytes ( Vincenzi et al, 2020 ). No studies have been reported analyzing the effect of PEMF on oligodendrocytes and pericytes which are also part of the neurovascular unit.…”
Section: Discussionmentioning
confidence: 99%
“…Even though in Vincenzi’s study astrocyte cultured media did not affect viability in neuron cells under OGD conditions ( Vincenzi et al, 2020 ), other authors have proven that OGD-astrocyte conditioned media alone could augment neuronal death ( Jin et al, 2017 ) and decrease microglia cell death ( Redzic et al, 2015 ). Thus, EMF experiments where culture media is collected in cell cultures subjected to OGD or other stimuli mimicking the ischemic processes should also be performed because all cell types of the neurovascular units are affected after a stroke.…”
Section: Effect Of Emfsmentioning
confidence: 93%
See 3 more Smart Citations